Online Learning Impressions on Students' Psychology at Madrasah Ibtidaiyah - Muhammad Mushfi El Iq Bali; Dwi Astutik (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2023)
This study describes in detail the online learning impression on student's psychology. This study used a qualitative research approach with a case study type. The data sources were interviews with twenty informants: the principal, one teacher, nine parents, and nine students at Madrasah Ibtidaiyah in Probolinggo. Based on the study's results, there were three categories of the online learning impressions on the students' psychology; cognitive, affective, and conative domain. Students' cognitive domain, students who can not solve problems well and have had a low level of understanding of students' material, students' knowledge of technology is getting wider. In the affective domain, emotional stability was disturbed, such as students being stressed, worried, afraid, dependent on gadgets, and bored with online learning. The conative domain was the intensity of communication with good parents and the lack of socializing with peers.